Vancomycin is a risk factor for acute pancreatitis and increases the mortality rate in patients with severe pancreatitis - Wang, Yongxiang; He, Hongye; Heng, Zou; Liu, Zhongtao; Wen, Yu (Frontiers in Immunology, 2026)
BackgroundIn the later stages of severe acute pancreatitis, serious infections often occur, leading to a worse prognosis. Vancomycin is beneficial for controlling infections, but it has hepatotoxic and nephrotoxic effects.MethodsData regarding the toxic side effects of vancomycin were obtained from the FDA Adverse Event Reporting System (FAERS), and animal experiments were conducted to validate these findings.Clinical data of patients with severe pancreatitis were extracted from the MIMIC database. Subsequently, the survival and matching packages were utilized to perform propensity score matching to assess the impact of vancomycin on patient prognosis. Finally, the mediation package was employed to analyze the clinical factors that mediate the effect of vancomycin on prognosis.ResultsData from the FAERS database and animal studies suggest that vancomycin may harm pancreatic tissue. Consequently, the administration of vancomycin in patients with severe pancreatitis increases their risk of mortality. In the Intensive Care Unit (ICU), the mediation effects of potassium, total bilirubin, hemoglobin, age, and lactate on the relationship between vancomycin use and prognosis in severe pancreatitis were found to account for 7.07%, 5.58%, 6.51%, 16.68%, and 10.37% of the total effect, respectively. Furthermore, during the 28 days prior to ICU admission, the mediation effects of age, hemoglobin, red cell distribution, hematocrit, CO2 concentration, urea nitrogen, levofloxacin, creatinine, and heart failure accounted for 18.47%, 10.39%, 13.63%, 6.69%, 5.74%, 20.07%, 7.39%, -66.04%, and 6.82% of the total effect, respectively, concerning the same variables.ConclusionVancomycin may induce pancreatic injury and elevate the risk of mortality in patients with severe pancreatitis. Moreover, renal function, patient age, heart failure, and red blood cell-related indicators are significant mediating factors.